Anton Wilhelm Amo (1703-1756) the African‐German philosopher of mind: an eighteen-century intellectual history - Emma-Adamah, Victor U. (University of the Free State, 2015)
Abstract not available
Dissertation (M.Th. (Jonathan Edwards Centre Africa))--University of the Free State, 2015
Keywords: Amo, Anton Wilhelm -- approximately 1700-approximately 1754; Philosophy, African; Philosophy, African -- 18th century